2015
DOI: 10.1155/2015/954120
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Dynamic Biological Characteristics of Sca-1+Hematopoietic Stem and Progenitor Cell Senescence

Abstract: The researches in the dynamic changes of the progress of HSCs aging are very limited and necessary. In this study, male C57BL/6 mice were divided into 5 groups by age. We found that the superoxide damage of HSPCs started to increase from the middle age (6 months old), with notably reduced antioxidation ability. In accordance with that, the senescence of HSPCs also started from the middle age, since the self-renewal and differentiation ability remarkably decreased, and senescence-associated markers SA-β-GAL inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Specifically, it has been reported that aberrant increases in ROS can disrupt HSC quiescence by stimulating entry into the cell cycle, which comprises the ability of the HSCs to self-renew and leads to premature exhaustion [ 34 36 ]. Our previous study showed that superoxide damage was accumulating in the HSCs with the natural progress of aging [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, it has been reported that aberrant increases in ROS can disrupt HSC quiescence by stimulating entry into the cell cycle, which comprises the ability of the HSCs to self-renew and leads to premature exhaustion [ 34 36 ]. Our previous study showed that superoxide damage was accumulating in the HSCs with the natural progress of aging [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed for a long time that with advancing age, the number of HSCs decreases, which leads to deficiency in hematopoiesis and immunity in company of diseases related with aging. Our recent studies have shown that, with increasing age, the antioxidant capacity of HSCs remarkably decreases and superoxide accumulates, finally causing HSC senescence [3]. As the core component of HIM, as to whether BMMSCs can also manifest age-related senescence like HSCs can, there have been few reports concerning this.…”
Section: Introductionmentioning
confidence: 99%
“…Among these 11 regulators, Cxcl12 was identified as the most dramatically increased in the GFP + cells isolated from the YS + chimeric hearts, especially after the induction of MI. Cxcl12 is of interest because it plays an important role in BM stem cell retention, mobilization, homing, and survival (Geng et al, ). Cxcl12 exerts its effects by binding the receptors Cxcr7 and Cxcr4, for which it is a unique ligand.…”
Section: Resultsmentioning
confidence: 99%